Bi-objective mathematical model for optimal sequencing of two-level factorial designs - Pureza, V. M.M.; Oprime, P. C.; Costa, A. F.B. [UNESP]; Morales, D. (Institute of Mathematical Statistics, 2020)
Conducting sequencing experiments with good statistical properties and low cost is a crucial challenge for both researchers and practi-tioners. The main reason for this challenge is the combinatorial nature of the problem and the possible conflicts among objectives. The problem was addressed by proposing a mathematical programming formulation aimed at generating minimum-cost run orders with the best statistical properties for 2k full-factorial and fractional-factorial designs. The approach performance is evaluated using designs of up to 64 experiments with different levels of reso-lution. The results indicate that the approach can yield optimal or sub-optimal solutions, depending on the objectives established for a given design matrix.
Keywords: Combinatorial optimization; Design of experiments; Linear time trend; Mathematical pro-gramming; Systematic sequencing